The Likelihood of Arrest: A Routine Activity Theory Approach - Drawve, Grant R. (American journal of criminal justice, 2014)
Routine activities theory (RAT) is traditionally drawn upon to highlight the role of offender motivation, target suitability, and effective guardianship in explaining victimization patterns. While an extensive literature base supports RAT, prior studies have neglected to examine the impact of offender motivation, target suitability, and guardianship on diverse outcomes of violent crimes. The current study extends prior research grounded in RAT by exploring the role of indicators of the central elements highlighted by the theory in understanding the likelihood that an offender will be arrested. As such, this study adds to the growing body of literature on RAT by exploring its relevance to a more diverse set of outcomes. To do this, we draw on the wealth of data on offender, victim, and incident characteristics available in the National Incident Based Reporting System (NIBRS). Results from the analysis offer a moderate to strong level of support for extending RAT to understanding variation in the likelihood that an offender will be arrested. The insights gained from a RAT framework were further discussed in relation to our findings.